The Possible Barriers behind Reflective Thinking and Practice: Experiences of School Principals from Turkey and Denmark - (:unkn) unknown (EDAM, 2013)
The possible barriers behind reflective thinking and practices of school principals were aimed to be determined with this study. The study is a qualitative study based on phenomenology. Data was collected from 37 school principals (24 from Istanbul, 13 from Copenhagen) who were serving in a variety of secondary schools (gymnasium) in Istanbul and Copenhagen during 2009-2010. The study shows the qualities of international education research. Data were collected using semi-structured interviews, and content analysis was used in data analysis. Restricted by the experiences of participants of the study, the possible barriers behind school principals' reflection were determined as internal (staticity, inclination of authority establishment, not having a command of a foreign language, teaching/not teaching as a teacher) and external barriers (conciliation culture, isolation and lack of networking, constant changes in the system and workload, centralism, parental indifference, teacher burnout). In the light of the study findings, recommendations were devised for candidates of educational administration, principals, policy makers and researchers to aid the development of reflective thinking skills and practices.
Keywords: School Principal; Reflective Thinking; Reflective Practice; Barriers